Robust Direct Adaptive Controller Design for Photovoltaic Maximum Power Point Tracking Application - M. Bani Salim; H. S. Hayajneh; A. Mohammed; S. Ozcelik (Energies, 2019)
Tracking the maximum output power of a photovoltaic (PV) cell is an important problem to harvest more energy at different weather and load conditions. This paper presents the design and simulation of a robust direct adaptive controller (RDAC) for maximum power point tracking (MPPT) device based on boost converter topology. A mathematical model is developed, and a suitable RDAC is designed for MPPT device, and simulations are performed using MATLAB/Simulink to verify the controller’s robustness at varying operating conditions. The real-time irradiance and temperature data are used on an hourly basis to test the suggested MPPT adaptive controller for a typical sunny day in summer and winter. The simulation results show that the RDAC performs excellent tracking under varying conditions such as irradiance, temperature, load, boost converter inductance, and capacitance.